Vanished at Present, a Group of Names and Family Names Given in Georgian Legal Documents of Medieval Centuries - Kekua, Sophio (Actual Problems of Kartvelology, 2019)
Georgian legal documents of medieval centuries are very important for studying the origin of Georgian names and family names. In this respect, the date given in the 17th century annals, which covers the historical Odish-Abkhazian territory, happened to acquire special importance for us. Our aim, to find spread in that time, names and family names of Georgian origin, in historical Odish-Abkhazia territory, is partially achieved. The analyses of legal documents show that many names and family names registered in medieval centuries do not exist today. At this stage of the studies, 36 names spread in the 17th century historical Odish-Abkhazian territory have been revealed. According to the present data none of them are found. Hereby we would like to mention that the analyses of the vanished names and family names haven’t been finished yet. There is still much to study, which is a matter for the future.